PENGARUH GREEN INVESTMENT, GREEN STRATEGY, TAX AVOIDANCE, DAN FIRM VALUE TERHADAP CARBON EMISSION DISCLOSURE - Fitri Wulandari; Silvi Rahmadi; Sri Agustina; Linawati Linawati (Asosiasi Dosen Muda Indonesia, 2025)
This study examines the influence of green investment, green strategy, tax avoidance, and firm value on carbon emission disclosure among companies listed in the ESGSKEHATI index in Indonesia. Using secondary data from annual and sustainability reports, the analysis applies a random effects panel regression to assess how environmental and financial factors drive corporate transparency in disclosing carbon information. The findings reveal that both green investment and green strategy have a positive and significant impact on the extent of carbon emission disclosure, indicating that proactive environmental initiatives and sustainability-oriented management contribute to improved corporate accountability. Conversely, tax avoidance and firm value show no significant effect, suggesting that environmental disclosure is more closely linked to sustainability commitment than to fiscal or market incentives. The study emphasizes the strategic importance of integrating environmental responsibility into corporate governance for long-term credibility and investor confidence.